INOVASI PRODUK LEMBAGA KEUANGAN SYARIAH DALAM MENDORONG INKLUSI KEUANGAN DI NEGARA-NEGARA BRICS (BRAZIL, RUSIA, INDIA, TIONGKOK DAN AFRIKA SELATAN) - Khofsah, Sholihatin (AL-MANSYUR, 2025)
Abstract: strategies and challenges that will be faced by Islamic financial institutions in innovating products to encourage financial inclusion in countries that are members of BRICS (Brazil, Russia, India, China and South Africa). Strategies and challenges for innovating to increase the attractiveness and accessibility of financial products for the community and to make a real contribution to poverty alleviation and improving the economic welfare of the community. The method used in this study is a descriptive qualitative method. with secondary data collection to determine the strategies and challenges of Islamic financial institutions in encouraging financial inclusion. The results of the study on Islamic Financial Institution Product Innovation in Encouraging Financial Inclusion in BRICS Countries (Brazil, Russia, India, China and South Africa) are: (1) The challenges of developing digital Islamic finance in BRICS countries face complex challenges that require attention and collaborative efforts to overcome the obstacles that will be faced. (2) The strategy for developing digital Islamic financial innovation in BRICS requires a comprehensive approach by considering aspects of regulation, technology, products, education, and collaboration. By optimizing existing potential, BRICS countries can create a strong and sustainable Islamic financial ecosystem.